Anti-LGI1 encephalitis and co-existence of MOG-IgG: a case report and literature review - Ci, Xiaojiao; Lin, Liuyu; Wu, Yuqing; Ma, Yifang; Lu, Jie (Frontiers in Human Neuroscience, 2025)
BackgroundAnti-leucine-rich glioma-inactivated-1 (LGI1) encephalitis is an autoimmune disorder characterized by antibodies that target LGI1 (LGI1-IgG). It typically presents with cognitive impairment, psychiatric disturbances, and faciobrachial dystonic seizures (FBDS). Myelin oligodendrocyte glycoprotein antibody-associated disease (MOGAD) is currently recognized as a demyelinating disease of the central nervous system (CNS) mediated by antibodies against myelin oligodendrocyte glycoprotein (MOG-IgG). The co-occurrence of anti-LGI1 encephalitis and MOG-IgG is a rare phenomenon.MethodsWe report a case of anti-LGI1 antibody encephalitis combined with MOG-IgG. A comprehensive literature search was conducted using the PubMed and Embase databases. We utilized the following search terms: (“Limbic Encephalitis”[MeSH Terms] OR (“autoimmune encephalitis”[Title/Abstract] OR “AE”[Title/Abstract])) AND (“Myelin-Oligodendrocyte Glycoprotein”[MeSH Terms] OR “demyelinating autoimmune diseases, cns”[MeSH Terms] OR (“MOG-IgG”[Title/Abstract] OR “MOGAD”[Title/Abstract])). The search was constrained to the period from January 1, 2010, to December 31, 2024.ResultsA total of nine papers involving 11 patients were included in the study. Three patients exhibited MOG-IgG in combination with LGI1-IgG. The majority of cases presented with encephalopathic symptoms. Visual changes were observed in a few cases with low titers of serum MOG-IgG or solely in the presence of MOG-IgG in the cerebrospinal fluid (CSF).ConclusionThe occurrence of anti-LGI1 encephalitis alongside MOG-IgG is a relatively rare phenomenon. The clinical manifestation of encephalopathy in patients with coexisting antibodies presents a significant challenge for clinicians regarding timely diagnosis, highlighting the need for increased vigilance in daily practice.